Outward foreign direct investment and domestic innovation performance: evidence from China - Zhou, C.; Hong, J.; Wu, Y.; Marinova, Dora (2018)
The existing literature has explored the existence of reverse technology spillover through outward foreign direct investment (OFDI), which means domestic firms improve their technological innovation and productivity due to overseas investment activities. This paper aims to examine how the host country affects reverse technology spillover from OFDI. The findings show domestic innovation performance (DIP) is positively related to OFDI in developed countries while it is negatively related to OFDI in transitional and emerging markets. It is also found that financial development and human capital weaken the positive relationship between OFDI in developed countries and DIP and also weaken the negative relationship between OFDI in transitional and emerging markets and DIP. These results are further confirmed through robustness checks.